Supporting Spartina: Interdisciplinary perspective shows Spartina as a distinct solid genus. Issue 11 (19th September 2019) - Bortolus, Alejandro; Adam, Paul; Adams, Janine B.; Ainouche, Malika L.; Ayres, Debra; Bertness, Mark D.; Bouma, Tjeerd J.; Bruno, John F.; Caçador, Isabel; Carlton, James T.; Castillo, Jesus M.; Costa, Cesar S. B.; et al.
Abstract: In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus, including (among others) species previously included in the genera Spartina, Calamovilfa, and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .